Penyuluhan Body Shaming di SMA Negeri 1 Darul Imarah Aceh Besar - Khairun, Afina Afiyati; Equatora, Muhammad Ali; Zulyadi, Teuku; Saputra, Hijrah (CV. Literasi Indonesia, 2023)
Body Shaming is a form of social action that negatively impacts individuals. The action is in the form of insults that have a negative impact on the mental health of individuals. This counseling was held at SMA Negeri 1 Darul Imarah Aceh Besar. This activity was carried out because in this high school, there are classes that often occur bullying including body shaming both to teachers and fellow students. This counseling was carried out by presenting, explaining, and opening a question-and-answer session related to body shaming material. This activity increases students' understanding of body shaming and understands the impact of body shaming and how to overcome it. It is hoped that students will avoid and realize the negative impact of body shaming so that their mental health of students is maintained.